The development of multifunctional sulfated polyguluronic acid-based polymeric micelles for anticancer drug delivery. (1st March 2023) - Qiu, Xiaolei; Ma, Shengzhou; Wang, Dingfu; Fan, Zirui; Qiu, Peiju; Wang, Shixin; Li, Chunxia
Abstract: Numerous disseminated tumor cells specifically overexpress P-selectin. Therefore, it was thought to be a potential target for tumor therapy. Herein, we described a novel P-selectin-targeted glycosyl ligand-sulfated polyguluronic acid (PGS), as an oriented carrier of P-selectin-targeted drug delivery system. Specifically, the PGS-SS-DOX polymeric micelles were constructed to confirm the practicability of the PGS carrier as a new P-selectin-targeted ligand. PGS-SS-DOX micelles comprised P-selectin-targeted PGS, doxorubicin (DOX) as an anticarcinogen, and pH/redox dual-sensitive bio-linker facilitating drug release in tumor tissues. In vitro and in vivo data showed that PGS-SS-DOX micelles significantly increased tumor cell killing capacity and exhibited a favorable biocompatibility comparison with Free-DOX. This work proved that PGS was an ideal low immunogenic, biodegradable drug carrier for the delivery of anti-cancer drugs. The facile PGS-SS-drug micelle system provided enormous opportunities for treating disseminated tumors utilizing many irreplaceable anticarcinogens. Graphical abstract: Unlabelled Image